Exam Ref SC-300 Microsoft Identity and Access Administrator - Rais, Razi (MICROSOFT, 2022)
Prepare for Microsoft Exam SC-300 and demonstrate your real-world ability to design, implement, and operate identity and access management systems with Microsoft Azure Active Directory (AD). Designed for professionals involved in secure authentication, access, or identity management, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified: Identity and Access Administrator Associate level. Focus on the expertise measured by these objectives: Implement identities in Azure AD Implement authentication and access management Implement access management for applications Plan and implement identity governance in Azure AD This Microsoft Exam Ref: Organizes its coverage by exam objectives Features strategic, what-if scenarios to challenge you Assumes that you are an administrator, security engineer, or other IT professional who provides, or plans to provide, secure identity and access services for an enterprise About the Exam Exam SC-300 focuses on the knowledge needed to configure and manage Azure AD tenants; create, configure, and manage Azure AD identities; implement and manage external identities and hybrid identity; plan, implement, and manage Azure Multifactor Authentication (MFA), self-service password reset, Azure AD user authentication, and Azure AD conditional access; manage Azure AD Identity Protection; implement access management for Azure resources; manage and monitor app access with Microsoft Defender for Cloud Apps; plan, implement, and monitor enterprise app integration; enable app registration; plan and implement entitlement management and privileged access; plan, implement, and manage access reviews; and monitor Azure AD. About Microsoft Certification Passing this exam fulfills your requirements for the Microsoft Certified: Identity and Access Administrator Associate certification, demonstrating your abilities to design, implement, and operate identity and access management systems with Azure AD; configure and manage identity authentication and authorization for users, devices, resources, and applications; provide seamless experiences and self-service; verify identities for Zero Trust; automate Azure AD management; troubleshoot and monitor identity and access environments; and collaborate to drive strategic identity projects, modernize identity solutions, and implement hybrid identity and/or identity governance. See full details at: microsoft.com/learn.